2003
DOI: 10.1016/s0014-5793(03)01030-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of NDRG2 (N‐myc downstream regulated gene 2) during the differentiation of dendritic cells

Abstract: We searched for genes with expressions speci¢c to human monocyte-derived dendritic cells (DCs) using di¡erential display reverse transcription-polymerase chain reaction, and found that N-myc downstream regulated gene 2 (NDRG2), a member of a new family of di¡erentiation-related genes, was expressed in DCs. While DCs derived from CD34 + progenitor cells also showed strong NDRG2 expression, the corresponding mRNA expression was absent in other cell lines including monocytes, B cells, and NK cells. The inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 48 publications
4
72
0
Order By: Relevance
“…Included in this group are N-myc downstream regulated gene 2 (Cluster 6), pigment epitheliumderived factor (Cluster 6), transmembrane protein semaphorin 6C (Cluster 4) and slit-1 (Cluster 6) (Wu et al, 1999;Qu et al, 2002;Choi et al, 2003;Deng et al, 2003;Wang et al, 2003). The last two genes are particularly interesting since both have been typically associated with inhibiting nerve cell migration (Wu et al, 1999;Qu et al, 2002), and our findings suggest that these same genes may hinder cancer cell motility.…”
Section: Discussionmentioning
confidence: 83%
“…Included in this group are N-myc downstream regulated gene 2 (Cluster 6), pigment epitheliumderived factor (Cluster 6), transmembrane protein semaphorin 6C (Cluster 4) and slit-1 (Cluster 6) (Wu et al, 1999;Qu et al, 2002;Choi et al, 2003;Deng et al, 2003;Wang et al, 2003). The last two genes are particularly interesting since both have been typically associated with inhibiting nerve cell migration (Wu et al, 1999;Qu et al, 2002), and our findings suggest that these same genes may hinder cancer cell motility.…”
Section: Discussionmentioning
confidence: 83%
“…NDRG2 expression is upregulated in cortical pyramidal neurons, senile plaques, and the cellular process of dystrophic neurons in the Alzheimer's brain, whereas expression is decreased in the rat frontal cortex after antidepressant treatment and electroconvulsive therapy (11). NDRG2 also plays a role in aldosterone-mediated epithelial sodium channel function (12), dendritic cell differentiation (13), and insulin action (14). NDRG3, on the other hand, may play a role in spermatogenesis because it is found in the outer layers of the seminiferous epithelium (3).…”
Section: N-myc Downstream-regulated Gene (Ndrg)mentioning
confidence: 99%
“…Northern blot analysis was performed according to a previously described method (Choi et al, 2003). The NDRG2 probe was prepared from the RT-PCR product using a specific primer set; 5'-ATGGCGGAGCTGCAGG-3' and 3'-TCAACAGGAGACCTCCAT-5'.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…NDRG2 has been implicated in cell growth (Deng et al, 2003), differentiation (Choi et al, 2003), and apoptosis (Zhou et al, 2001). It has also been reported that NDRG2 is rapidly responsive to mineralocorticoid stimuli in the kidney (Boulkroun et al, 2002).…”
Section: Introductionmentioning
confidence: 99%